Kontribusi Alokasi Pendapatan dan Belanja Desa (APBDesa) Pada Indeks Pembangunan Manusia (IPM) Satu Keresidenan Bojonegoro - Hening Anitasari; Khalid Fauzi Aziz; Yustika Arida Putri (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This research aims to determine the contribution and influence of the Village Income and Expenditure Allocation (APBDesa) on the Human Development Index (HDI) in Bojonegoro Residency. The method used is descriptive-quantitative, which is intended to explain the results of research regarding the influence caused by the variables. Secondary data in this research is data that has been statistically processed and sourced from information on the Bojonegoro Residency Human Development Index for the period 2017–2021. Data analysis uses an analysis tool in the form of eviews with a multiple linear regression analysis model, namely classic assumptions, regression testing, and hypothesis testing. The research results show that the three districts that contribute to the human development index, namely Lamongan District, are seen through the variables of village income and village expenditure. Meanwhile, partial and simultaneous test results have significant results and influence the human development index in Lamongan Regency. So from these results, it can be said that not all districts in the Bojonegoro residency related to the Village APBD have an effect on the human development index.